Filtration anisotropy in terrigenous collectors and its influence on oil field development (Western Siberia deposits); SGEM. 17th International Multidisciplinary Scientific GeoConference; Vol. 17, iss. 14 - Krasnoshchekova L. A. Lubov Afanasievna (2017, 2017)
Title screen